Condutividade elétrica, envelhecimento acelerado e atividade enzimática em sementes de sorgo sacarino - Dalcin, Joner Silveira (2015)
The objective of this study was to analyze the quality of sweet sorghum seeds and their biochemical and physiological relationships by the tests of electrical conductivity, accelerated aging and activity of ezymes. Four seed lots were analyzed for each cultivar BRS 506 and F-19 separately. The physical and physiological quality were evaluated by the moisture content, weight of a thousand seeds and germination, first count of germination, length of radicle and aerial portion, dry weight, cold test and seedling emergence in the field and later were subjected to the following experiments: i: electrical conductivity mass with variations in immersion time (2, 4, 6, 8, 12 and 24 hours), temperature (20, 25 and 30 ° C), number of seeds (25 and 50), water volume (50 ml and 75); ii: Individual electrical conductivity variations in the soaking time (2, 4, 6, 8, 12 and 24 hours); iii: artificial accelerated aging using variations in temperature (41, 43 and 45 ° C) and storage time (48, 96 and 120 hours); and iiii: activity of the enzymes superoxide dismutase (SOD) and guaiacol peroxidase (POD) to root and aerial portion. The experiments were conducted in a completely randomized design and were assessed by comparison of means by the Scott-Knott test for enzymes and Tukey test for the other variables. The results obtained in electrical conductivity conclude that: a) it was possible to detect only the low vigor lot of the F-19 cultivar, especially in combinations using a temperature of 20 ° C, 75 mL and 25 seeds; b) there was no stratification of lots by the physiological quality on BRS 506 depending on the similarity between batches; c) the individual electrical conductivity test was efficient in detecting the lot of low physiological quality for both cultivars, and it can be accomplish in 24 hours in both cultivars. The results of the accelerated aging test and enzyme activity can be concluded that: a) the accelerated aging was sensitive to detect differences between the lots and their relation to physiological quality; b) at a temperature of 43 ° C and 96 hours were related with the best potential physiological quality of the lots; c) the enzyme activity was specific for each seedling body, with lower activity of SOD in roots and increased activity in the aerial portion, and POD enzyme, increased activity in the roots and lower activity in the aerial portion; d) the quality of the lots of each cultivar seeds influenced the activity of enzymes SOD and POD; e) 45 ° C and 96 hours was detrimental to the enzymes decreasing their activity.